Hubungan Pola Asuh dan Disiplin Belajar dengan Hasil Belajar di Sekolah Dasar - Profithasari, Nindy; Loliyana, Loliyana; Hermawan, Jody Setya; Destini, Frida; Fadila, Khairunnisa Okta Melina (Didaktika, 2023)
The ability of students to take part in learning can be seen from their learning outcomes. Student learning outcomes can be influenced by internal and external factors. One of the external factors that affect learning outcomes is parenting and learning discipline. The purpose of this study was to describe the relationship between parenting and learning discipline with the learning outcomes of fourth grade elementary school students. The type of research used is quantitative research with ex post facto method. The population in this study amounted to 171 students, with a total sample of 66 students determined by the proportionate stratified random sampling technique. The data in this study were collected through documentation, interviews, and questionnaires. The research data were then analyzed using product moment correlation and multiple correlation. The results showed that there was a positive and significant relationship between parenting and learning discipline with learning outcomes with a correlation coefficient of 0.641 which was at the "high" level.